DISTRIBUTING COVID-19 RELIEF FUNDS IN NIGERIA: PERSPECTIVES FROM JOHN RAWLS’ DISTRIBUTIVE THEORY OF JUSTICE - Paul T. Haaga (PREDESTINATION: Journal of Society and Culture, 2021)
This paper argues that every responsible government has an obligation, to the best of its ability, to ensure an adequate provision of economic welfare and healthcare for its citizens. In view of this global pandemic, the Nigerian government, like many other nations, has urgently developed a plan to provide health and economic assistance to the tens of millions of people who are vulnerable. However, the provision of these palliatives by the government designed to assuage the effect of the COVID-19 pandemic on the poor and vulnerable Nigerians is not fairly undertaken. Adopting an expository and analytic approach, this paper examines the role of the government in distributing the COVID- 19 relief funds; in doing this, the questions in this paper are in two fronts: firstly, what constitutes vulnerability and who is vulnerable? Secondly, what is the criterion adopted by the government for determining who benefits from these palliatives? Finally, the paper proposes a model for assessing the role of government in the distribution of palliatives from the prism of John Rawls’s principle of distributive justice. This is imperative because the fair distribution of relief funds and benefits from the government will further ease the burdens, and it will fundamentally affect the people’s wellbeing.